An Analysis of Classroom English Teachers’ Questioning Types - Putri, Azura Mulyani; Riza, Armilia; Ikhsan, Muhammad Khairi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
AbstractThis research aims to identify the types of questions used by English teachers in the classroom, focusing on convergent and divergent questions. Therefore, the researcher employed a descriptive qualitative research method for this study. The participants in this research were two English teachers at SMP Negeri 1 Lubuk Sikaping, Pasaman. Each teacher was responsible for teaching eighth-grade classes. The research data were collected using a video recorder to record the teaching and learning process in the classroom. The researcher conducted observations by using a video recorder as a tool during the observation process. The results of the data analysis from the observations revealed that English teachers at SMP Negeri 1 Lubuk Sikaping, Pasaman, utilized both convergent and divergent questions during the learning process. However, in practice, teachers more frequently used convergent questions compared to divergent questions to guide and stimulate students' critical thinking.Keywords: Teachers’ Questions, Convergent Questions, Divergent Questions AbstrakPenelitian ini bertujuan untuk melihat tipe-tipe pertanyaan guru bahasa inggris didalam kelas yang berfokus pada pertanyaan konvergen dan divergen. Oleh karena itu peneliti menggunakan metode descriptive qualitative research untuk penelitian ini. Partisipasi dalam penelitian ini adalah dua orang guru bahasa inggris SMP Negeri 1 lubuk Sikaping, Pasaman. Masing-masing guru mempunyai tugas mengajar dikelas delapan. Data penelitan dikumpulkan menggunakan alat perekam video (video recorder) untuk merekam proses pembelajaran dikelas. Peneliti melakukan observasi dengan menggunakan observation (video recorder) sebagai alat selama observasi. Hasil analisis data observasi menunjukkan bahwa guru Bahasa Inggris di SMP Negeri 1 Lubuk Sikaping, Pasaman, menggunakan pertanyaan konvergen dan divergen selama proses pemnelajaran. Namun, dalam praktiknya, guru lebih sering menggunakan pertanyaan konvergen dibandingkan dengan pertanyaan divergen untuk membimbing dan menstimulasi pemikiran kritis siswa.Kata kunci: Pertanyaan Guru, Pertanyaan konvergen, Pertanyaan divergen